Numerical investigation of the operating conditions affecting nitrogen condensation on a three-dimensional wing in the cryogenic wind tunnel - Jiaxin Hou; Junlong Xie; Xi Pan; Jianye Chen (Engineering Applications of Computational Fluid Mechanics)
Cryogenic wind tunnels (CWT) perform high Reynolds number aerodynamic tests in a cryogenic environment and simulate hypersonic flights. However, condensation under cryogenic conditions presents a major challenge to test’s reliability. The detailed conditions remain unclear, and traditional strategies for reducing condensation in CWT need further exploration. In this paper, an Euler-Euler two-phase flow model is established based on the classical nucleation approach and the droplet growth theory, and also presents a method for the three-dimensional transonic flow modelling. This model integrates thermodynamic properties with aerodynamic behaviour to provide a reliable simulation approach. A series of operating conditions are simulated, involving three distinct Reynolds numbers. The simulated results revealed that condensation on the wing wall is caused by two main factors: the low-pressure region at the leading edge due to the angle of attack and the pressure drop due to an airflow expansion beyond the wing’s thickest section. Subsequently, the key operating conditions that influence the condensation phenomena are identified using Correlation Matrix Analysis and Principal Component Analysis. Furthermore, this study identifies the critical regions where condensation occurs under high Reynolds number flight conditions. The findings contribute to refining operational strategies in CWT, offering improved guidelines that minimise condensation risks under varied conditions.Highlights The effects of various operating conditions on condensation were simulated.The three-dimensional characteristics were described during condensation process.Operating pressure is identified as a key factor in CWT condensation phenomena.A critical area was proposed to support optimal conditions and avoid condensation.